THE USE OF PICTURE GAMES TO IMPROVE STUDENTS’ MOTIVATION IN LEARNING VOCABULARY (Universitas Negeri Semarang, 2013)
This research aims at investigating the use of picture games which used by English teacher in learning vocabulary in the classroom of State Elementary School 01 Rancawuluh. This research focused on the problems faced by students in learning vocabulary, picture games applied, students’ motivation, students’ achievement in learning vocabulary. The results show that the students felt difficulty in receiving lesson material which taught by teacher because lack of vocabulary mastery, and students’ motivation were still low. In applying Picture Games, the researcher did three cycles aims to reduce the problems faced by students in learning vocabulary, to improve motivation, and to improve students’ achievement in vocabulary mastery. In the first cycle students’ motivation were still low those were 54%, second cycle 68.3%, and the third cycle 93% it means that every cycle increase significantly. This research also show that students’ achievement in learning vocabulary through Picture Games in the first cycle the average was 54.2, second cycle 60 and the third cycle 77.3. The result of the study indicates that the use of Picture Games, the students felt happy so that the motivation and students’ achievement were improved.